The rapid determination of bromadiolone in liver and blood plasma by in-injector pyrolysis gas chromatography - Ion trap tandem mass spectrometry - Doubková, Veronika; Maršálek, Petr; Večerek, Vladimír (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2017)
The unintentional poisoning of off-target animals by bromadiolone, a second generation anticoagulant rodenticide, is an undesirable outcome requiring sensitive analytical methods. In this study, a rapid and sensitive method for the determination of bromadiolone in liver and blood plasma by means of gas chromatography coupled with tandem mass spectrometry without need for derivatization was developed. The method is based on the in-injector pyrolysis of bromadiolone and subsequent gas chromatography coupled with ion trap tandem mass spectrometry with electron ionization. Sample preparation includes extraction with methanol, evaporation under nitrogen stream, and dissolution in toluene. The pyrolysis of bromadiolone was carried out in an injector at 390°C. Chromatographic separation of the pyrolytical fragment of bromadiolone was achieved using a VF-5ms column with helium as the mobile phase. Tandem in-time mass spectrometry of the separated pyrolytical fragment of bromadiolone was carried out using an ion trap mass spectrometer after electron ionization. Recovery ranged from 94 to 98%. The method showed good linearity up to 1000μgkg-1 for liver and 1000μgL-1 for plasma. The limit of detection was 0.38μgkg-1 for liver and 0.26μgL-1 for plasma. The developed method was used successfully in several animal poisoning cases.
Keywords: Liver; Animals; 4-hydroxykumariny; Electron ionization; játra; Linear Models; GC/MS; Reproducibility of Results; prasata; lineární modely; reprodukovatelnost výsledků; limita detekce; Poison; Swine; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; Rodenticides; Limit of Detection; 4-Hydroxycoumarins; zvířata; rodenticidy